GLP-1/Exendin-4 induces β-cell proliferation via the epidermal growth factor receptor - Joseph Fusco (Nature Portfolio, 2017)
Abstract Exendin-4 is a long acting glucagon-like peptide 1 (GLP-1) analogue that is an agonist for the GLP-1 receptor, a G-protein coupled receptor (GPCR). Exendin-4 is used to clinically improve glucose tolerance in diabetic patients due to its ability to enhance insulin secretion. In rodents, and possibly in humans, exendin-4 can stimulate β-cell proliferation. The exact mechanism of action to induce β-cell proliferation is not well understood. Here, using a β-cell specific epidermal growth factor receptor (EGFR) null mouse, we show that exendin-4 induced an increase in proliferation and β-cell mass through EGFR. Thus, our study sheds light on the role of EGFR signaling in the effects of exendin-4 on the control of blood glucose metabolism and β-cell mass.